2006
DOI: 10.1121/1.2335422
|View full text |Cite
|
Sign up to set email alerts
|

Formant transitions in fricative identification: The role of native fricative inventory

Abstract: The distribution of energy across the noise spectrum provides the primary cues for the identification of a fricative. Formant transitions have been reported to play a role in identification of some fricatives, but the combined results so far are conflicting. We report five experiments testing the hypothesis that listeners differ in their use of formant transitions as a function of the presence of spectrally similar fricatives in their native language. Dutch, English, German, Polish, and Spanish native listener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
3
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 29 publications
4
57
3
2
Order By: Relevance
“…A more important reason for the lack of an interaction between listener groups and listening conditions, however, seems that, whereas Dutch listeners made more errors than English listeners did, the differences between those listener groups were not notably larger (and sometimes even smaller) in noise than in quiet (A ppendix). Cutler et al (2008) found similar results, and argue that this can be explained by the finding that English listeners rely more than Dutch listeners do on transitional cues, which do not survive well under noise, for fricative identification (Wagner et al, 2006). Indeed, in general, the identification performance in quiet does not seem to determine which phonemes did and which ones did not show a differential effect of noise for L1 and L2 listeners.…”
Section: Discussionmentioning
confidence: 94%
“…A more important reason for the lack of an interaction between listener groups and listening conditions, however, seems that, whereas Dutch listeners made more errors than English listeners did, the differences between those listener groups were not notably larger (and sometimes even smaller) in noise than in quiet (A ppendix). Cutler et al (2008) found similar results, and argue that this can be explained by the finding that English listeners rely more than Dutch listeners do on transitional cues, which do not survive well under noise, for fricative identification (Wagner et al, 2006). Indeed, in general, the identification performance in quiet does not seem to determine which phonemes did and which ones did not show a differential effect of noise for L1 and L2 listeners.…”
Section: Discussionmentioning
confidence: 94%
“…The result that Japanese listeners rely more on transitional information such as onset F2 frequency may also be explained by the conclusions of Wagner et al (2006). In their study, Wagner et al tested the role of formant transitions in fricative perceptions in five languages: Dutch, German, Spanish, English, and Polish, which differ in their fricative inventories.…”
Section: Discussionmentioning
confidence: 95%
“…Particularly sibilants, i.e. the research subject of the present study, "have very pronounced spectral peaks" [7].…”
Section: Background: the Notion Of "Segmental Intonation"mentioning
confidence: 99%
“…Alternatively (or additionally), it is possible that formant transition residuals of the original sibilant are irrelevant perceptually as long as there is no phonetically closely related neighboring phoneme, i.e. a "spectrally confusable fricative" in the terminology of Wagner et al [7]. Wagner et al found that misleading formant transitions created by fricative cross-splicing in pseudowords did not affect the identification rate of /s/ and /ʃ/ for German listeners, because the two fricatives are too different from each other to be spectrally confusable.…”
Section: Effects Of Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation